1983
DOI: 10.1128/iai.42.2.639-644.1983
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae soluble hemagglutinin/protease is a metalloenzyme

Abstract: A soluble hemagglutinin/protease produced by Vibrio cholerae, which has previously been shown to hydrolyze fibronectin and ovomucin and to cleave lactoferrin and the A subunit of the heat-labile enterotoxin of Escherichia coli, appears to be a zinc metalloendopeptidase. Both its hemagglutinative and protease functions are inhibited by chelating agents, including Zincov, a hydroxamic acid derivative specifically designed to inhibit zinc metalloproteases. Thermolysin, a known zinc-containing protease, also cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 18 publications
(33 reference statements)
2
31
0
Order By: Relevance
“…1). The purified protease was biochemically and physicochemically identical to HA/protease, as previously reported by Booth et al [3] and Honda et al [7]. The hemagglutinin activity of purified protease, however, was not detected as previously reported [15].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…1). The purified protease was biochemically and physicochemically identical to HA/protease, as previously reported by Booth et al [3] and Honda et al [7]. The hemagglutinin activity of purified protease, however, was not detected as previously reported [15].…”
Section: Resultssupporting
confidence: 85%
“…It was also reported by Finkelstein et al [5] that a soluble zinc-and calcium-dependent protease from V. cholerae O1 causes hemagglutination, hydrolyzes mucin and cleaves and degenerates lactoferrin and secretary IgA. Crowther et al [6] demonstrated that a metalloprotease in V. cholerae culture filtrates identical to that described previously by Booth et al [3] enhanced the activity of cholera enterotoxin in intestinal loops by eroding the protective layer of the epithelial mucous. The digestion of the mucosal layer by protease may facilitate bacterial intestinal colonization, which is an initial step for infection, and thereby result in the enhancement of virulence.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition to V8 protease, S. au reus secretes at least two other proteases, staphopain (papain-like thiol protease) (2) and aureolysin (typical metalloproteinase) (I). These proteases also encompass enzymes including Pseudomonas aeruginosa elastase (23), Legionella pneumophila (18) and Listeria monocytogenes metalloproteinases (9), Vibrio cholerae hemagglutinin protease (5), Staphylococcus epidermidis elastase (32), and the lambda toxin of Clostridium perfringens (20), which are acknowledged as virulence factors. Moreover, a recent study indicated that staphylococcal proteases exerted a decisive influence on influen-Abbreviations: CBB, Coomassie brilliant blue; CHAPS, 3-[(3-cholamidopropyl) dimethylammonio] propanesulfonic acid; 2-DE, two-dimensional polyacrylamide-gel electrophoresis; DTT, dithiothreitol; lPG, immobilized pH gradient; Oklahoma data base, genome sequence data base constructed in the University of Oklahoma's Advanced Center for Genome Technology; PVDF, polyvinylidene difluoride; SDS, sodium dodecyl sulfate; SDS-PAGE,sodium dodecyl sulfate-polyacrylamide gel electrophoresis; TCA, trichloroacetic acid; TSS, toxic-shock syndrome.…”
mentioning
confidence: 99%
“…The secreted HA/P has been characterized as a zinc-dependent metalloprotease [22] with the ability to cleave several physiologically important substrates, including mucin, ¢bronectin, and lactoferrin [23]. It also nicks and activates CT and CT-related enterotoxins [24].…”
Section: Resultsmentioning
confidence: 99%